An efficient identification scheme in standard model based on the diophantine equation hard problem - Tea, Boon Chian; Kamel Ariffin, Muhammad Rezal; Chin, Ji Jian (Institute for Mathematical Research, Universiti Putra Malaysia, 2013)
Recently the Diophantine Equation Hard Problem (DEHP) was proposed. It is utilized to design a standard identification scheme model. Since the computation involves only simple addition and multiplication steps, the efficiency and the time cost are greatly improved as compared to the existing identification schemes. In this paper, we propose a zero knowledge identification scheme based upon the DEHP. With the assumption such that DEHP is intractable, we provide the security analysis on the impersonation against non-adaptive passive attack (imp-pa) and show that our new proposed scheme is more desirable due to high efficiency in terms of time computation.